Status report on primary health care - Bautista, Victoria A. (1995)
Everybody has a right to health care. More importantly, it is enshrined in the 1987 Philippine Constitution that the State shall safeguard the health of the people. The full realization of the primary health care policy of the Department of Health is a big stride towards the direction of providing basic health services to the masses.
Keywords: Medical care; Philippine Health Care; Community health services